Sosialisasi Motif dan Filosofi Batik kepada Pelajar SD melalui Pendekatan Edukatif - Andrianti, Nafadilla Sri; Yuliani, Novita Dita; Indriana, Mei Sofa; Awwalia, Luthfi (Jurnal Solutif: Jurnal Pengabdian Masyarakat, 2024)
Batik is an Indonesian cultural heritage that has high artistic value and rich in philosophy. However, the younger generation's awareness of batik, especially among elementary school students, is still relatively low. This research aims to develop an effective educational approach in socializing the various motives and philosophy of batik to elementary school students. The approach involved interactive learning methods through visualization stories and interactive question-and-answer discussions designed to foster children's appreciation and understanding of batik. The result shows the increasing students' experiences and perspectives in understanding the uniqueness and philosophical meaning behind each batik motif. This educational approach is expected to strengthen cultural identity from an early age and build a sense of pride in the nation's cultural heritage.